Onset of the COVID-19 pandemic reduced active time in patients with implanted cardiac devices. - Sommers, Nicholas; Berger, Marcie; Rubenstein, Jason C.; Roth, James; Pan, Amy; Thompson, Colton; Widlansky, Michael E. (European Review of Aging & Physical Activity, 2022)
Background: Physical inactivity and sedentary behavior are modifiable risk factors for chronic disease and all-cause mortality that may have been negatively impacted by the COVID-19 shutdowns. Methods: Accelerometry data was retrospectively collected from 332 permanent pacemaker (PPM) and 244 implantable cardiac defibrillation (ICD) patients for 6 time points: March 15-May 15, 2020 (pandemic period), January 1-March 14, 2020, October 1-December 31, 2019, March 15-May 15, 2019, January 1-March 14, 2019, and October 1-December 31, 2018. Paired t-tests, with Bonferroni correction, were used to compare time periods. Results: Activity significantly decreased during the pandemic period compared to one year prior by an average of 0.53 ± 1.18h/day (P < 0.001) for PPM patients and 0.51 ± 1.2h/day (P < 0.001) for ICD patients. Stratification of subjects by active time (< 2 versus ≥ 2h/day) showed patients with < 2h, particularly those with ICDs, had modestly greater activity reductions with the pandemic onset. Logistical regression analyses suggest a trend toward a greater reduction in active time at the onset of the pandemic and an increased risk of hospital or emergency department (ED) admission for PPM patients, but not ICD patients. Conclusion: The onset of the pandemic in the United States was associated with a significant drop in PPM and ICD patient active hours that was modestly more pronounced in less active patients and cannot be explained by one year of aging or seasonal variation. If sustained, these populations may experience excess cardiovascular morbidity.